Letter - Pankhurst, E. Sylvia (Estelle Sylvia), 1882-1960
027-0050-001 New Times and Ethiopia News (WEEKLY) Editor: E. SYLVIA PANKHURST All Communications to: "WEST DENE" 3 CHARTERIS ROAD WOODFORD GREEN ESSEX : ENGLAND Telephone: BUCkhurst 2463. Your Ref. Our Ref. Advisory Board: NANCY CUNARD A. EIDENSCHENK-PATIN General Secretary: International League of Mothers and Educators for Peace Ancien Membre Consell Supérieur de l'Instruction publique. ISABEL FRY PHILIP HOPKINS Chairman, West of England Abyssinia Association. Dr. HUGENHOLTZ President, Dutch Society for the Liberation of Ethiopia. F. L. LUCAS ROSIKA SCHWIMMER Colonel MAURICE SPENCER Rev. V. ZIAPKOFF President, Union of Young People's Evangelical Associations in Bulgaria. 26th October, 1939. ESP/GC. Sir Walter Citrine, Transport House, Smith Square, Westminster, S.W.1. Dear Sir Walter Citrine, I write on behalf of Guiseppe Gatti, No. 5665, Brixton Prison, a Spanish refugee. I understand that he was in touch with the police through the Labour Party, but as I can only consider was a mistake, he was arrested and sent to Brixton Prison. I understand he is willing to do any work of national importance or take any part that the Home Office may direct, to assist Britain in the struggle against Nazi domination, just as he fought against the Hitler regime when he was in the army of the Government of Spain. I trust that you will kindly use your influence to procure his release and to play his part in the struggle. Yours sincerely, E. Sylvia Pankhurst. P.S. I understand he is a trade unionist and came to England with credentials to the Labour Party. [shorthand] 292/946/27/50